Nanostructured tin oxide materials as photoanode for dye sensitized solar cells - Qamar, Wali (2016)
Photoanode plays vital role in the operation of dye sensitized solar cells (DSSCs) owing to its many fold functions: (i) as a substrate to anchor dye, (ii) enable the bound electron-hole pair formed in the dye to be separated into mobile charge carriers, and (iii) provide a medium to accept and transport the photoinduced electrons. Although TiO2 nanoparticles (NPs) is the most successful employed photoanode material in DSSCs delivering efficiency (η) ~14.3% due to its high specific surface area (~150 m2/g), it is characterized by slow electron diffusion and mobility (µe). On the other hand, SnO2 shows an outstanding performance in many electronic devices owing to its higher µe. The high µe could transport electrons much faster and minimize the charge recombination in the device. From this point of view, SnO2 is an interesting alternative to that of TiO2. In this research, NPs and multifunctional NPs-Nanospheres (NPs-NSs) were synthesized hydrothermally by simply varying the hydrothermal annealing temperature from 150 to 200 °c. The multifunctional (NPs-NSs) shows higher crystallinity and superior light scattering in comparison to NPs analogue because of its unique morphology i.e., the size of the spheres in the range of ~800 nm – 1 m which are comparable to the visible light wavelength. The photovoltaic (PV) parameters include short circuit density (JSC), open circuit voltage (VOC) and  were higher for the multifunctional (NPs-NSs) i.e., 17 mA cm–2, 500 mV and ~4.0% vs. 7, 370 and ~1.3 for NPs analogue, respectively. For the superior charge transport, on the other hand, various one dimensional electrospun nanomaterials were synthesized. A strategy was adopted by just keeping the precursor concentration changing while other constituents of the solution constant. Among them, multiporous nanofibers (MPNFs) resulted in a significantly higher JSC ~18 mA cm–2 compared to that of porous NFs (PNFs) ~10 mA cm–2 due to 8-10-folds larger surface area of the former, which consequently adsorbed large amount of dye. However, the fill factor (FF) and VOC were limited to (~45-50%) and (~450-500 mV) in pure SnO2 based DSSCs, respectively. Finally, the lower VOC and FF were enhanced using a composite by incorporating TiO2 NPs into SnO2 photoanode via TiCl4 treatment. This technique considerably improved the VOC (from ~500 to 720 mV) and similarly JSC from (~17 to 22 mA cm–2). Though VOC and JSC increased dramatically, the FF was still limited to ~50%. In the second approach, an electrospun composite (SnO2-TiO2) NFs was used as photoanode, which yielded VOC (~730 mV) and FF (~60%) simultaneously, closer to that of TiO2 (Voc ~700-800 mV and FF ~60-68%). Results of this research provide promising directions such as increasing surface area and surface roughness of the composite nanofibers so that efficiency levels for practical applications could be realized.